(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines contemporary language teaching methods and explores practical ways to enhance their effectiveness in diverse learning environments. It provides an overview of widely used approaches such as communicative language teaching, task-based learning, and learner-centered instruction, highlighting how they respond to the changing needs of modern learners. The study concludes that combining traditional pedagogical principles with modern techniques can significantly improve both teaching quality and learner engagement.